Administration of Pumpkin Seeds Herbal Capsules (Cucurbita Moschata) and Iron Supplement Tablets to Increase Serum Ferritin Levels in Pregnancy Anemia - Ika Yuni Susanti; Sri Rahayu; Diyah Fatmasari (Journal Of Nursing Practice, 2026)
Background: Iron deficiency anemia is the most common hematological problem, affecting approximately 38% of pregnant women globally. Pregnant women who take oral iron supplements often complain of gastrointestinal problems. The 2021 Household Health Survey (HHS) found the prevalence of iron deficiency anemia among pregnant women in Indonesia was 24.5%. Purpose: The aim of this study was to examine the effect of addition of pumpkin seed capsules (Cucurbita moschata) to increase serum ferritin levels in pregnant women with anemia. This type of research is a true ex- experimental study with a pretest-posttest with a control group. Methods: Serum ferritin test method using the ELFA method (enzyme-linked fluorescent immunoassay). The blood sample for the test is 1 ml of serum. The limit of iron deficiency anemia with a value of <9.3 µg/mL. The study period was September-October 2024. Results: The results of the Wilcoxon test showed a Significance value (Sig) in the group given pumpkin seed capsules obtained a ρ value of 0.00 1 smaller than α 0.05, thus concluding that pumpkin seed capsules (Cucurbita moschata) have an effect on increasing serum ferritin levels in pregnant women with anemia. Conclusion: Pumpkin seeds can be a non-pharmacological remedy for increasing hemoglobin levels if consumed regularly. One effort that can be made to prevent anemia in pregnant women is to utilize local plants as functional foods found around the community's residence.